„Nie będę śmierci nabijać licznika”. Fragmenty dziennika pandemicznego Wioletty Grzegorzewskiej - Wolski, Jan (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
This article attempts to characterize the published fragments of Wioletta Grzegorzewska’s diary from the beginning of the covid-19 pandemic and to evaluate its cognitive and artistic value. It takes a global literary tradition which has existed since ancient times, reflecting on the topics of various catastrophes affecting individual people and entire societies, into account. The hardships of everyday life, dreams and illusions accompanying them are framed as a work showing the features of specific genres: diary, sylvia and reportage.
“I won’t raise the Number on Death’s counter”. Fragments of Wioletta Grzegorzewska’s Pandemic Diary
Keywords: pandemic; pandemic literature; diaries and journals; pandemia; literatura pandemiczna; dzienniki i pamiętniki